杂多酸铵盐催化剂及其制法 (2019)
本发明公开了一种杂多酸铵盐催化剂及其制法。该催化剂包括活性组分、助剂及载体，活性组分为杂多酸铵盐，助剂为镍、磷和钒，载体为无定形硅铝包覆的分子筛，以载体的重量为基准，助剂以氧化物计，PO的含量为3.0%~10.0%，VO的含量为0.2%~4.0%，NiO的含量为8%~20%；以催化剂的重量为基准，杂多酸铵盐的含量为8%~30%，助剂以氧化物计和载体的总含量为70%~92%。本发明催化剂具有较高的低温活性、选择性和抗积炭性能的同时，改善了催化剂的稳定性。本发明催化剂特别适用于低浓度乙醇水溶液为原料的脱水制乙烯反应。 The present invention discloses a heteropolyacid ammonium salt catalyst and a preparation method thereof. The catalyst comprises an active component, auxiliary agents and a carrier, wherein the active component is a heteropolyacid ammonium salt, the auxiliary agents are nickel, phosphorus and vanadium, the carrier is an amorphous silicon-aluminum coated molecular sieve, the auxiliary agents comprise (calculated as the oxide) 3.0-10.0% of P2O5, 0.2-4.0% of V2O5 and 8-20% of NiO by adopting the weight of the carrier as the reference, the heteropolyacid ammonium salt content is 8-30% by adopting the weight of the catalyst as the reference, and the total content of the auxiliary agents and the carrier is 70-92% (calculated as the oxide). According to the pre